THE USE OF SENSORY TEXTILE BOOKS TO ENCOURAGE CREATIVITY AMONG PRESCHOOL CHILDREN: A CASE STUDY - Theresa Goh Shi Qian; Lai Yi Lin; Kasturi A/P Pormalu @ Perumal (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Sensory textile books are usually made of fabric materials that allow pre-school and young children to interact and play by touching and feeling them, that encourage creativity to their neurodevelopment. This research aims to summarise the findings of how sensory textile books encourage healthy development and growth of the body and mind which can stimulate creativity, imagination, and motor skills among preschool children. The study compared whether the use of sensory textile books encouraged creativity between the preschool children in the General Kindergarten and Montessori Kindergarten. The researchers used a qualitative method where semi-structured and open-ended interviews were conducted with the experts. The expert teachers were selected based on their educational qualifications. The first two experts have Diplomas in Montessori English, and the third expert as Master’s in Teaching and Learning. Interviews were conducted with the three experts to ascertain which method of learning impacted more the preschool children. The result showed that the children who grew up with hands-on Montessori learning method tend to be much more creative later in their lives. The Montessori Kindergarten method used natural interests and activities that manipulated the muscle to perform tasks, much unlike the formal teaching among preschool children in General Kindergarten. The Montessori system encouraged hands-on learning experiences which is the foundation of creativity and imagination. The present review revealed that sensory textile books played an essential role in the healthy development of preschool children, especially in the first five years of their lives. Therefore, the implementation of Montessori system, use of sensory books made of textile materials can be helpful and can be introduced in the Malaysian kindergarten system. Future researchers can consider integrating Montessori learning in the syllabus of preschool children to encourage creativity, imagination, and motor development from a young age. Activities in the sensory books can be designed to train motor skills with simple mechanics for pre-school children. This research will allow other research designers to develop better sensory books to promote creativity and imagination for pre- school children.